Investigation of antimicrobial susceptibility patterns, risk factors and their impact on mortality in cancer patients at a tertiary care cancer hospital- A prospective study - Akshay Shelke; Pallavi Priya; Shiwani Mishra; Richa Chauhan; Krishna Murti; V. Ravichandiran; Sameer Dhingra (BMC, 2024)
Abstract Background Cancer patients are vulnerable to infections due to immunosuppression caused by cancer itself and its treatment. The emergence of antimicrobial-resistant bacteria further complicates the treatment of infections and increases the mortality and hospital stays. This study aimed to investigate the microbial spectrum, antimicrobial resistance patterns, risk factors, and their impact on clinical outcomes in these patients. Methods A prospective study was conducted at a tertiary care cancer hospital in Patna, Bihar, India, which included cancer patients aged 18 years and older with positive microbial cultures. Results This study analysed 440 patients, 53% (234) of whom were females, with an average age of 49.27 (± 14.73) years. A total of 541 isolates were identified, among which 48.01% (242) were multidrug resistant (MDR), 29.76% (150) were extensively drug resistant (XDR), and 19.84% (112) were sensitive. This study revealed that patients who underwent surgery, chemotherapy, were hospitalized, had a history of antibiotic exposure, and had severe neutropenia were more susceptible to MDR and XDR infections. The average hospital stays were 16.90 (± 10.23), 18.30 (± 11.14), and 22.83 (± 13.22) days for patients with sensitive, MDR, and XDR infections, respectively. The study also revealed overall 30-day mortality rate of 31.81% (140), whereas the MDR and XDR group exhibited 38.92% and 50.29% rates of 30-day mortality respectively (P < 0.001). Possible risk factors identified that could lead to mortality, were cancer recurrence, sepsis, chemotherapy, indwelling invasive devices such as foley catheter, Central venous catheter and ryles tube, MASCC score (< 21) and pneumonia. Conclusions This study emphasizes the necessity for personalized interventions among cancer patients, such as identifying patients at risk of infection, judicious antibiotic use, infection control measures, and the implementation of antimicrobial stewardship programs to reduce the rate of antimicrobial-resistant infection and associated mortality and hospital length of stay.